2013
DOI: 10.1096/fj.12-223867
|View full text |Cite
|
Sign up to set email alerts
|

Histamine production by human neutrophils

Abstract: Histamine is an important mediator in the development of allergic reactions. Only a small subset of human cell types is able to produce histamine. No previous studies have shown that human neutrophils are among them. The present work was undertaken to analyze whether human neutrophils produce histamine, and to determine what agonists are involved in histamine production by human neutrophils. The expression of histidine decarboxylase in human neutrophils was established by quantitative PCR, Western blotting, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 61 publications
2
51
0
Order By: Relevance
“…In particular, TLR2/4/6 genes were highly enriched in granulocytic myeloid cells (Figure 2B and S3C) (Table S1) (Chen et al, 2017). As LPS elicits histamine release from Hdc-expressing cells (Alcaniz et al, 2013), we analyzed histamine release from Hdc-GFPhi HSCs and myeloid cells in response to in vitro LPS stimulation. The results showed that only Hdc-GFP hi myeloid cells were capable of releasing a large amount of histamine shortly after LPS treatment (Figure S3D), indicating that Hdc-expressing myeloid cells preferentially sense and respond to bacteria-mediated TLR signals.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, TLR2/4/6 genes were highly enriched in granulocytic myeloid cells (Figure 2B and S3C) (Table S1) (Chen et al, 2017). As LPS elicits histamine release from Hdc-expressing cells (Alcaniz et al, 2013), we analyzed histamine release from Hdc-GFPhi HSCs and myeloid cells in response to in vitro LPS stimulation. The results showed that only Hdc-GFP hi myeloid cells were capable of releasing a large amount of histamine shortly after LPS treatment (Figure S3D), indicating that Hdc-expressing myeloid cells preferentially sense and respond to bacteria-mediated TLR signals.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the H 4 R has a very high affinity for histamine, especially compared with the histamine H 1 and H 2 receptors, and therefore it may be activated by cells that release even low levels of histamine. To this point, it has become apparent that many immune cells, such as dendritic cells, T cells and neutrophils, are capable of producing histamine when stimulated 7 30 31. It has been speculated that local production of histamine by dendritic cells can act in an autocrine fashion to modulate dendritic cell/T cell interactions,32 and this local production of histamine in the joint or at sites of T cell activation may be the most relevant for H 4 R activation in human arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…In mast cells, basophils, enterochromaffin-like cells of the gastrointestinal tract, and histaminergic neurons, histamine is stored, probably heparin-bound, in granules and is released in response to a specific stimulus (Barnes et al, 1988;Rabenstein et al, 1998). However, HDC is expressed not only in these "classically" known histamine-producing cells but also in monocyte-derived cells (László et al, 2000;Dunford et al, 2006;Xu et al, 2012;Alcañiz et al, 2013). As a consequence, one can speculate that HDC activity is present, at least after induction, in virtually every other cell type as well.…”
Section: Histaminementioning
confidence: 99%